Eosinophilic vacuolated tumor (EVT) of kidney demonstrates sporadic TSC/MTOR mutations: next-generation sequencing multi-institutional study of 19 cases - Farcaş, Mihaela; Gatalica, Zoran; Trpkov, Kiril; Swensen, Jeffrey; Zhou, Ming; Alaghehbandan, Reza; Williamson, Sean R; Magi-Galluzzi, Cristina; Gill, Anthony J; Tretiakova, Maria; Lopez, Jose I; Montiel, Delia Perez; et al. (Modern pathology, 2022)
A distinct renal tumor has recently been described as "high-grade oncocytic renal tumor" and "sporadic renal cell carcinoma with eosinophilic and vacuolated cytoplasm". The Genitourinary Pathology Society (GUPS) consensus proposed a unifying name "eosinophilic vacuolated tumor" (EVT) for this emerging entity. In this multi-institutional study, we evaluated 19 EVTs, particularly their molecular features and mutation profile, using next-generation sequencing. All cases were sporadic and none of the patients had a tuberous sclerosis complex. There were 8 men and 11 women, with a mean age of 47 years (median 50; range 15-72 years). Average tumor size was 4.3 cm (median 3.8 cm; range 1.5-11.5 cm). All patients with available follow-up data (18/19) were alive and without evidence of disease recurrence or progression during the follow-up, ranging from 12 to 198 months (mean 56.3, median 41.5 months). The tumors were well circumscribed, but lacked a well-formed capsule, had nested to solid growth, focal tubular architecture, and showed ubiquitous, large intracytoplasmic vacuoles, round to oval nuclei, and prominent nucleoli. Immunohistochemically, cathepsin K, CD117, CD10, and antimitochondrial antigen were expressed in all cases. Other positive stains included: PAX8, AE1/AE3 and CK18. CK7 was typically restricted only to rare scattered cells. Vimentin, HMB45, melan-A, and TFE3 were negative in all cases. All tumors showed retained SDHB. All cases (19/19) showed non-overlapping mutations of the mTOR pathway genes: TSC1 (4), TSC2 (7), and MTOR (8); one case with MTOR mutation showed a coexistent RICTOR missense mutation. Low mutational rates were found in all samples (ranged from 0 to 6 mutations/Mbp). Microsatellite instability and copy number variations were not found in any of the 17 analyzable cases. EVT represents an emerging renal entity that shows a characteristic and readily identifiable morphology, consistent immunohistochemical profile, indolent behavior, and mutations in either TSC1, TSC2, or MTOR genes.
Keywords: mutace; DNA Copy Number Variations; dospělí; Kidney; Female; TOR Serine-Threonine Kinases; Adult; mladý dospělý; ženské pohlaví; Neoplasm Recurrence, Local; High-Throughput Nucleotide Sequencing; Adolescent; variabilita počtu kopií segmentů DNA; lidé; karcinom z renálních buněk; Mutation; Kidney Neoplasms; Carcinoma, Renal Cell; Male; nádorové biomarkery; Aged; vysoce účinné nukleotidové sekvenování; Young Adult; lokální recidiva nádoru; nádory ledvin; Biomarkers, Tumor; lidé středního věku; senioři; mužské pohlaví; TOR serin-threoninkinasy; ledviny; Middle Aged; mladiství; Humans